What influences planted tree seedling survival in burned Colorado montane forests? - Marshall, Laura A.E.; Fornwalt, Paula J.; Stevens-Rumann, Camille S.; Rodman, Kyle C.; Chapman, Teresa B.; Schloegel, Catherine A.; Stevens, Jens T. (Forest ecology and management, 2024)
Across the western United States, large, severe wildfires in montane forests are creating treeless patches that can fail to reforest naturally due to a lack of seed sources and a warming climate. Nursery-grown tree seedlings are commonly planted by land managers into these areas to promote forest recovery and resilience, but uncertainty exists about what influences their survival across the landscape. We obtained survival monitoring data that had been collected one growing season after planting for 5656 tree seedlings, which were distributed across nine montane wildfires and four National Forests in Colorado, USA. We used these data to examine how seedling survival varied across a range of factors, including long-term average climatic conditions, post-planting weather conditions, and locations and species of seed lot collection. We found that survival after one growing season averaged 80 % across all plots but ranged from 0 % to 100 %. Survival was greater at cooler, wetter sites and at sites planted in warmer, wetter years. Survival was also greater for ponderosa pine than for Douglas-fir, and when the locally collected seed lot used to produce the seedlings came from a site that was lower in elevation than the planting site. Our results suggest that the location and timing of tree planting, and the plant materials used, play critical roles in planting success in Colorado montane wildfires, and should help land managers optimize post-fire planted seedling survival under both current and future climatic conditions. •Monitoring data were used to examine drivers of planted tree seedling survival.•Data were collected after one growing season in nine montane Colorado wildfires.•Survival was greater for ponderosa pine seedlings than for Douglas-fir seedlings.•Survival was greater at cool, wet sites and at sites planted in warm, wet years.•Survival increased when seed sources were lower in elevation than planting sites.